PHYSIOLOGICAL RESPONSES OF SHALLOT (Allium cepa L. Aggregatum group) IN DROUGHT STRESS WITH THE APPLICATION OF SALICYLIC ACID AND BIOSILICA - Indarwati, Lisa Dwifani; Sulistyaningsih, Endang; Zuhdi, AH. Maftuh Hafidh (Jurnal Agrotek Tropika, 2025)
The purpose of this study was to determine the physiological responses of shallots in drought stress with the application of salicylic acid and biosilica. The research was conducted in the Tri Dharma experimental station plastic house, Faculty of Agriculture, Universitas Gadjah Mada, located in Banguntapan District, Bantul, Yogyakarta, from November 2019 to May 2020. A factorial 4x2 experiment was laid out in a randomized complete block design with four blocks. The treatments were a four-level exogenous induction, i.e., 0,5mM SA, 6mM Si, a combination of 0,5 SA and 6mM Si, and control/0 exogenous induction by a two-level irrigation interval, i.e., one-day interval and three-day interval. The variables observed included leaf greenness, leaf and root surface area, plant fresh and dry weight, endogenous SA, POD enzyme activity, H2O2 levels, and yield components. The data were statistically analyzed using the analysis of variance with the honestly significant difference value, calculated as Tukey's statistic at the 5% level. The research results showed that a three-day irrigation interval did not significantly affect the growth and yield of the Bima Brebes shallot cultivar. Application of a combination of 0,5 mM SA and 6 mM Si can increase plant tolerance by accumulating higher levels of endogenous SA so that plants can maintain leaf greenness better than controls, increase bulb dry weight, harvest index, and shallot productivity, and significantly increase bulb diameter in three day-irrigation intervals.